ASPEK HUKUM PEMUTUSAN HUBUNGAN DIPLOMATIK BAHRAIN DENGAN QATAR BERDASARKAN KONVENSI WINA 1961 - Ade Khatibul Rafi; Jun Justinar (Reformasi Hukum Trisakti, 2022)
The unilateral termination of diplomatic relations by Bahrain to Qatar in 2017 was based on political elements that disturbed the national stability of Bahrain. Bahrain and Qatar are legally bound by the Vienna Convention because they ratified it. The main problems are whether the termination of diplomatic relations by Bahrain to Qatar is in accordance with the 1961 Vienna Convention and what are the legal consequences occured from the termination of diplomatic relations. The research is a normative and descriptive analytical legal research, with literature studies and the conclusions are drawn using deductive method. Secondary data obtain through library research and analyzed. The results of the research are as follows: 1) The termination of diplomatic relations between Bahrain and Qatar does not violate the provisions of the 1961 Vienna Convention because there is no standard stipulation that stipulates regulations regarding procedures for terminating diplomatic relations. 2) There are legal consequences that cause rights and obligations of each country as stipulated in Article 2 regarding Mutual Consent and Article 45 concerning the right of a sending country to surrendering trust to a third country regarding the supervision of a diplomatic representative building.